Biglycan regulates neuroinflammation by promoting M1 microglial activation in early brain injury after experimental subarachnoid hemorrhage. Issue 3 (15th December 2019) - Xie, Yuke; Peng, Jianhua; Pang, Jinwei; Guo, Kecheng; Zhang, Lifang; Yin, Shigang; Zhou, Jian; Gu, Long; Tu, Tianqi; Mu, Qiancheng; Liao, Yuyan; Zhang, Xianhui; et al.
Abstract: Neuroinflammation can be caused by various factors in early brain injury after subarachnoid hemorrhage (SAH). One of the most important features of this process is M1 microglial activation. In turn, the TLR4/NF‐κB pathway plays an essential role in activating M1 phenotypic microglia. Biglycan, a small leucine‐rich proteoglycan, functions as an endogenous ligand of TLR4 and TLR2 in macrophages. However, the underlying mechanisms associated with microglial activation in stroke pathogenesis are poorly understood. Here, we aimed to identify the role of biglycan in neuroinflammation following SAH. In our study, SAH was induced by endovascular perforation in young male C57BL/6J mice. Lentiviral vector was administered intracerebroventricularly to knock down Biglycan. Post‐SAH assessments included neurobehavioral tests, immunofluorescence, western blot, qRT‐PCR, Co‐IP, flow cytometry, and ELISA. The biglycan level was markedly elevated following SAH in vivo. Of particularly note, knockdown of biglycan significantly improved neurological outcomes. TLR4 was bound with soluble biglycan in vitro. In addition, biglycan down‐regulation suppressed the expression of phosphorylated‐NF‐κB p65 (p‐NF‐κB) and inducible nitric oxide synthase (iNOS), as well as the cytokine (TNF‐α, IL‐1β, and IL‐6) production in vivo and in vitro . Moreover, we detected a decreased expression of CD16/32 and CD86, M1 markers when biglycan was inhibited in vitro. Our work suggests that biglycan can induce neuroinflammation by promoting M1 microglial activation at least in part through TLR4/NF‐κB signaling pathway after experimental SAH. Targeting biglycan may be a promising strategy for the clinical management of SAH. Abstract : Biglycan, a small leucine‐rich proteoglycan, functions as an endogenous ligand of Toll‐like receptor 4 (TLR4) and could potently induce nuclear factor‐kappa B (NF‐κB) transcription. Our findings describe that biglycan is a critical regulator of M1 microglial polarization and mediates neuroinflammation via TLR4/NF‐κB signaling pathway in early brain injury (EBI) following subarachnoid hemorrhage (SAH) in mice. Knockdown of biglycan exerts neuroprotective effects against EBI, providing a novel strategy for SAH treatment.